HEALTH INEQUALITY AND SOCIAL DETERMINANTS: SOCIOLOGICAL PERSPECTIVES ON PUBLIC HEALTH POLICY - wijaya wijaya; Hassan Ali; Nurul Huda (Yayasan Adra Karima Hubbi, 2026)
Health inequality remains a persistent global challenge, influenced significantly by social determinants such as income, education, and access to healthcare. Sociological perspectives emphasize that these disparities are not merely the result of individual behaviors but are deeply embedded within social structures and systems. This research explores the impact of social determinants on health inequality and examines how public health policies address these factors. The study aims to assess how sociological insights can inform public health policies aimed at reducing health disparities, particularly in marginalized communities. A qualitative research design was employed, utilizing document analysis, in-depth interviews, and focus group discussions across various socio-economic groups. The findings indicate that socio-economic status and education are the most significant determinants of health outcomes, with individuals from lower-income and less-educated backgrounds facing higher rates of chronic diseases. Additionally, public health policies that integrate these social determinants have been more effective in addressing health inequalities than those focused solely on healthcare access. The study concludes that addressing the root causes of health disparities through sociologically informed policy frameworks is essential for reducing inequality and promoting more equitable health outcomes.